The Use of Contextual Video to Improve Students’ Ability in Writing Descriptive Text - Dewi Maharani, Maulina; Usman , Sriati; Agussatriana, Agussatriana; Anggreni, Afrillia (International Journal of Language Teaching and Education, 2026)
This study investigated the effectiveness of contextual video in improving eleventh-grade students’ ability to write descriptive texts at MAN 2 Kota Palu. A quasi-experimental design was employed involving an experimental class taught using contextual video and a control class receiving conventional instruction. Data were collected through pre-test and post-test writing tasks and analyzed using the Mann–Whitney U test. The pre-test results showed no significant difference between the groups (Sig. = 0.836 > 0.05), whereas the post-test results indicated a significant difference (Sig. = 0.004 < 0.05), with the experimental group achieving higher scores. The findings demonstrate that contextual video effectively improves students’ descriptive writing ability. This study extends previous research by explaining that contextual video supports descriptive writing through the integration of meaningful visual and verbal information, consistent with Multimedia Learning Theory. The findings provide practical and theoretical contributions to multimedia-based writing instruction in EFL classrooms.